Upaya Guru Pendidikan Agama Islam Membentuk Spiritual Quotient Peserta Didik di SMK PGRI 1 Kediri - Muhammad Khoirul Alfiansyah; Moh. Turmudi Abror; Abdulloh Haq Al-Haidary (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The objectives of this research include: (1) Analyzing the efforts of PAI (Islamic Education) teachers in shaping Spiritual Quotient (SQ) of students at SMK PGRI 1 Kediri; and (2) Analyzing the supporting and inhibiting factors for PAI teachers' efforts shaping the students' SQ at SMK PGRI 1 Kediri. The research method uses descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research subjects consisted of PAI teachers, the school principal, and students. The results of this study indicate that (1) PAI teachers have an important role shaping the Spiritual Quotient (SQ) of students at SMK PGRI 1 Kediri. These efforts are carried out through the habituation of religious activities, role modeling, and direct guidance. (2) Supporting factors include religious school culture and consistent religious programs, while obstacles arise from the low awareness of some students, environmental influences, time constraints, and lack of parental support. In conclusion, PAI teachers strive to shape SQ through the integration of spiritual values in practical daily activities, such as congregational prayers, reading the Qur'an, and giving alms. The teacher's role as role model, guide, and motivator is crucial in bridging the gap between theoretical understanding and real-world practice. A conducive school environment, such as a religious school culture and consistent programs, is a valuable asset in supporting the formation of SQ. The success of SQ formation greatly depends on the ability of PAI teachers to adapt, innovate, and collaborate with the entire school ecosystem including parents to overcome these obstacles. The findings of this research have direct implications for educational practices in vocational schools such as SMK PGRI 1 Kediri. PAI teachers can implement efforts such as daily worship habits and personal counseling to enhance students' SQ, which not only strengthens spiritual discipline but also helps students cope with academic and social pressures. This research contributes to expanding the SQ literature with an Islam-contextual perspective in the digital era, offering novelty through practical applications in SMKs and analysis of modern obstacles. This encourages further research to validate the SQ model in various school contexts, thereby enabling religious education to more effectively shape a spiritual and adaptive generation